1989
DOI: 10.1136/bmj.298.6672.483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social class, sex, and region of residence on age at death from cystic fibrosis.

Abstract: To determine the time trend in age at death from cystic fibrosis and the independent effects of social class, sex, and region of residence mortality data for England and Wales from 1959 to 1986 were analysed. Median age at death increased from 6 months in 1959 to 17 years in 1986 and was higher in most years from 1970 in male patients (by one to six years) and in social classes with non-manual occupations (by one to 12 years). Independent odds ratios for death above the median age for the year of death (calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 24 publications
3
51
1
2
Order By: Relevance
“…In New Zealand, the Christchurch Child Development Study also found that children from disadvantaged family back-grounds (measures used were maternal education, ethnicity, occupation, birth order, maternal age at birth) had an increased relative risk (2.72) of admission to hospital for accidents or infections and more general practitioner contacts [32]. Britton [33] in the U.K. found survival time for cystic fibrosis sufferers according to their parental occupational class.…”
Section: Socioeconomic Inequality and Severity Of Illnessmentioning
confidence: 99%
“…In New Zealand, the Christchurch Child Development Study also found that children from disadvantaged family back-grounds (measures used were maternal education, ethnicity, occupation, birth order, maternal age at birth) had an increased relative risk (2.72) of admission to hospital for accidents or infections and more general practitioner contacts [32]. Britton [33] in the U.K. found survival time for cystic fibrosis sufferers according to their parental occupational class.…”
Section: Socioeconomic Inequality and Severity Of Illnessmentioning
confidence: 99%
“…In 1986, there were 113 deaths registered of CF patients in the UK. Median age of death was 17 years overall, but it was above 20 for patients whose parents had a non-manual job whereas it was below 10 for the others (Britton et al, 1989). In a study of CF patients in the United States, the adjusted risk of death for indigent patients who qualified for Medicaid was 3.65 times higher than for those not receiving Medicaid.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…5) This is because subject-matter knowledge assures that there are no factors that are both strongly correlated with race and highly independently predictive of the outcome, and therefore no "setting" (i.e., physical manipulation) of the exposure is necessary. If we were to consider cystic fibrosis mortality as opposed to incidence, however, then this prima facie noconfounding assumption would no longer be tenable, because socioeconomic and other factors that are associated with race can clearly contribute to disease severity and medical care, which in turn affect mortality (Britton 1989, O'Connor et al 2002.…”
Section: The Analytic Epidemiologic Model Applied To Disparities Arismentioning
confidence: 99%